The Role of Extension Instructors on the Attitudes of Farmers in the Application of Inpari 32 Rice Seeds - Yolanda Gita Soraya; Siwi Gayatri; Kadhung Prayoga (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
One of the obstacles faced by the extension instructors (hereinafter referred to as ‘the instructors’) in providing extension is farmers’ lack of understanding about the innovation of Inpari 32 rice seeds due to their low education. The objectives of this study are (1) to analyze the role of instructors in the application of inpari 32 rice seeds, (2) to analyze the attitudes of farmers in the application of inpari 32 rice seeds, (3) to analyze the influence of the role of the instructors on farmers' attitudes in applying Inpari 32 rice seeds. The research was carried out on January 6 – 30, 2020 at Sari Tani Farmer Group 01. The research method used was a survey. The research location was chosen purposively. Purposive sampling was used in determining the respondents. The number of respondents was 32 people. Data collection methods used were interviews and observation. The data analysis method used was descriptive analysis and statistical analysis. The results showed that the role of the instructors as educators, innovators, motivators, and facilitators was categorized as high as the scale ranges were 100%, 78%, 100%, and 88%. The attitude of farmers in applying inpari 32 rice seeds based on the sapta usahatani (seven actions that farmers must take to generate maximum income) is categorized as high as the percentage scale range is 100%. The role of the instructors as educators and motivators has a partial effect on farmers' attitudes and the roles of the instructors as innovators and facilitators do not partially influence farmers' attitudes. The role of the instructors simultaneously influences the attitudes of the farmers.